2011
DOI: 10.1016/j.ajpath.2011.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-1 Promotes Angiogenesis, Fibrosis, and Portal Hypertension Through Mechanisms Dependent on Osmotically Sensitive MicroRNAs

Abstract: Changes in hepatic vasculature accompany fibrogenesis, and targeting angiogenic molecules often attenuates fibrosis in animals. Aquaporin-1 (AQP1) is a water channel, overexpressed in cirrhosis, that promotes angiogenesis by enhancing endothelial invasion. The effect of AQP1 on fibrogenesis in vivo and the mechanisms driving AQP1 expression during cirrhosis remain unclear. The purpose of this study was to test the effect of AQP1 deletion in cirrhosis and explore mechanisms regulating AQP1. After bile duct liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 48 publications
(48 reference statements)
2
35
0
3
Order By: Relevance
“…However, despite their recognized roles in embryo implantation, how the dynamic expression of miRNAs is controlled during implantation remains elusive. Although it has been reported that miRNAs are sensitive to environmental/extracellular cues, such as osmolality (Huebert et al 2011), pH (Lu et al 2012), and mechanical forces (Mohamed & Boriek 2010, Qin et al 2010, the exact mechanisms responsible for linking extracellular signals to changes in miRNAs are largely unexplored. Interestingly, as membrane proteins with signal transduction capacity, ion channels have been proposed to be candidate epigenetic regulators in linking extracellular signals to miRNA alterations in the cell .…”
Section: Discussionmentioning
confidence: 99%
“…However, despite their recognized roles in embryo implantation, how the dynamic expression of miRNAs is controlled during implantation remains elusive. Although it has been reported that miRNAs are sensitive to environmental/extracellular cues, such as osmolality (Huebert et al 2011), pH (Lu et al 2012), and mechanical forces (Mohamed & Boriek 2010, Qin et al 2010, the exact mechanisms responsible for linking extracellular signals to changes in miRNAs are largely unexplored. Interestingly, as membrane proteins with signal transduction capacity, ion channels have been proposed to be candidate epigenetic regulators in linking extracellular signals to miRNA alterations in the cell .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Guo et al confirmed that miR-126 might be used in reducing intrahepatic vascular resistance and in improving hepatic microcirculation [143]. miR-666 and miR-708 influenced the post-transcriptional of aquaporin-1 and subsequently mediated osmolar changes to reverse angiogenesis, fibrosis and portal hypertension [144]. Nevertheless, the research and application of miRNAs directly on relieving portal hypertension have been rarely reported.…”
Section: Signature Mirna Expression Profile Of Hypertensionmentioning
confidence: 99%
“…Human HEK 293 cells were grown in Dulbecco's modified Eagle's medium with 10% serum. Primary liver endothelial cells were obtained from C57Bl/6J and Klf14 Ϫ/Ϫ mice as previously described (19). Klf14 Ϫ/Ϫ mice were generated at the Mayo Transgenic and Gene Targeted Mouse Shared Resource facility using ES cells engineered by University of CA Davis Knock-out project to carry a 1035-bp deletion encompassing the complete, intronless, coding region of this gene.…”
Section: Methodsmentioning
confidence: 99%